Mykhaylo Apollonovych Arshulik - of Orthopedic Traumatologists, Ukrainian Association (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
On September 26, 2019, at the age of 57, after a short serious illness, the heart of the outstanding Ukrainian orthopedic traumatologist, chairman of the Volyn cell of the All-Ukrainian public organization Ukrainian Association of Orthopedic Traumatologists, Mykhailo Apollonovich Arshulik, stopped beating.